Impact of Formative Feedback on Students’ Problem-Solving Performance in Mathematics: A Study in Secondary Level Students in Dolakha District, Nepal - Dahal, Prem Prasad; Kafle, Bhuban; G.C., Laxmi (Journal of Mathematics Education, 2026)
This study intends to study the relationship of teacher given formative feedback and problem solving performance of the students in mathematics at secondary level in Dolakha District, Nepal. A quantitative cross-sectional survey design was adopted and data was collected from 228 students (Grade ten) who were selected from five secondary schools (three public and two private), a rural - semi-urban district context. A structured questionnaire measuring three constructs Formative Feedback Practices (FFP), Problem Solving Performance (PSP) and Perception of Feedback (POF) using a five point Likert scale was used. Descriptive statistics showed quite high mean scores of FFP (M = 3.98, SD = 0.66), PSP (M = 4.10, SD = 0.55) and POF (M = 3.91, SD = 0.84) with acceptable internal consistency (Cronbach’s alpha being in the range of .69 to .75). Pearson product-moment correlation analysis indicated that there were strong and positive relationships between FFP and PSP (r=.80, p<.001), FFP and POF (r=.72, p=.001) and POF and PSP (r=.71, p=.001).The results indicate that as well as having positive perceptions of feedback, students who indicated more frequent, clear and constructive formative feedback also indicated greater engagement in mathematical problem-solving activities. Although the allocation of causal relationships is impossible to infer from the results, they are suggestive of the potential importance of formative feedback in supporting reflections and strategy-oriented problem solving in secondary mathematics classrooms. The research recommends the need for strengthening of structured feedback practices and continuous teacher professional development for better formative assessment practices in the studied context.